"Borges and I," A Narrative Sleight of Hand - Armando F. Zubizarreta (Studies in 20th & 21st Century Literature, 1998)
Because of its autobiographical appearance, critics have paid little attention to the narrative of "Borges and I" which is so masterfully handled that its complex and transparent texture is almost invisible. A close analysis shows, however, that, in the confessional mode, the two individuals—I and Borges—are true characters involved in a narrative action that is taking place to allow the implementation of vengeance. By focusing on his victim's experience, the narrating I offers an attractive bait to his victimizer, Borges. Borges, the writer, driven by a compulsive pattern of stealing, unsuspectingly takes over the victim's grievances against him by virtue of his own writing. To unveil those basic elements of narrative at play in this short story, the participation of an active reader, as witness to the process and as recipient of the indicting text, is actually demanded. Thus, "Borges and I" may be considered a superb example of Jorge Luis Borges's art.
Keywords: autobiographical; Borges and I; complex; vengeance; narrative action; narrative; victimizer; Borges; short story; victim; Jorge Luis Borges; art